PKM2-driven metabolic reprogramming in digestive system tumors: mechanisms, therapeutic advances, and clinical challenges - Huang, Xinyao; He, Jianjun; Sun, Haonan; Wu, Yi; Gu, Renjun; Li, Ziyun (Frontiers in Immunology, 2025)
Metabolic reprogramming is a central driving force in the malignant progression of digestive system tumors. It facilitates tumor proliferation, metastasis, and therapeutic resistance through aerobic glycolysis, disordered lipid metabolism, and altered amino acid metabolism. Pyruvate kinase M2 (PKM2) functions as a key regulator of tumor metabolism, promoting aerobic glycolysis and suppressing mitochondrial respiration via conformational changes and nuclear translocation. These processes are orchestrated by hypoxia-inducible factors and oncogenic signaling, ensuring a sustained energy supply and biosynthetic precursors for tumor growth. Additionally, PKM2 modulates lipid biosynthesis and amino acid metabolism by participating in epigenetic regulation and the organization of metabolic enzyme complexes. These functions contribute to tumor adaptation within the microenvironment and promote immune evasion. In digestive system tumors, the regulatory network of PKM2 demonstrates tissue specificity, mediated by non-coding RNAs, post-translational modifications, and crosstalk between metabolic and signaling pathways, collectively sustaining metabolic plasticity. Therapeutic strategies targeting PKM2 primarily aim to reverse the Warburg effect or inhibit compensatory metabolic pathways; however, their clinical translation remains challenging. The dual regulatory role of PKM2 may perturb immunometabolic homeostasis; the fluctuating nutrient landscape of the tumor microenvironment can drive adaptive resistance; and some inhibitors exhibit limited specificity or unacceptable toxicity. This review summarizes the molecular mechanisms through which PKM2 drives metabolic reprogramming in digestive system tumors, as well as the current therapeutic advances and clinical barriers.